Permission to use prohibited and unclean items and its role in Islamic economy - Abolfazl Alishahi G; Bi Bi Zeinab Hosseini; Isa Tamini (Universitas Hayam Wuruk Perbanas, 2018)
The ruling prohibiting the use of prohibited and unclean items is found in the Holy Qur'an and the hadiths from the infallible imams (AS). The jurists consider the cause of the ruling of permission and prohibition of things to be their benefits and harms. The question is whether such benefits and harms making up the prohibition and permission of the use are fixed and permanent or they may change in the nature and subject matter? In the past, due to the lack of scientific and technical advancements, the benefits and uses of the prohibited items were not discovered or, in those circumstances, such uses were not possible, but the harmful aspect of prevailed. A number of jurists have categorically prohibited the use of prohibited and unclean items. Others, however, believe that in some cases, such as necessity, duress, etc., their use is permissible. A third group of jurists also believe that such uses are subject to conditions. With regard to the dynamic nature of Islamic jurisprudence, the role of time and place, and the change in the subject matter of the rulings and their instances in ijtihad, it would seem possible to issue a permission to use such items; so that in this way, solutions can be provided in cases such as treatment, job creation, and industry prosperity as well as the release from economic and livelihood bottlenecks.